Analiza efektywności wymiany ciepła w wymiennikach otworowych o różnej konstrukcji - Śliwa, Tomasz; Gonet, Andrzej (My University, 2011)
There are described in the paper drilling of borehole heat exchangers (BHE) on the world and in Poland. The most popular constructions of BHE are described with possibility of heat extraction. There are also showed results of calculation of effective heat transfer coefficient of the Laboratory of Geoenergetics of Drilling, Oil and Gas Faculty of AGH University of Science and Technology BHEs with its heat resistivity. This parameters decided for energetic efficiency of the BHEs.

W publikacji opisano realizacje otworowych wymienników ciepła na świecie i w Polsce. Zaprezentowano podstawowe konstrukcje wymienników otworowych. Przedstawiono możliwości wymiany ciepła. Podano obliczenia przewodności cieplnej efektywnej wymienników otworowych Laboratorium Geoenergetyki WWNiG AGH w Krakowie, a także wartości oporności termicznej wymienników, które mają wpływ na efektywność energetyczną.
Heat transfer efficiency analysis in different constructions of borehole heat exchangers
Wiertnictwo, Nafta, Gaz
Keywords: borehole heat exchangers; geoenergetics; otworowe wymienniki ciepła; heat pumps; geoenergetyka; pompy ciepła; geothermics; geotermia